1993
DOI: 10.1111/j.1440-1827.1993.tb03230.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry of neuronal inclusions in the cerebral cortex and brain‐stem in Lewy body disease

Abstract: Three cases of Lewy body disease were investigated in order to compare the morphological and immunohistochemical characteristics of the neuronal inclusions in the cerebral cortex (CC) and brain‐stem (BS). Ultrastructurally, the CC contained intermediate‐sized filaments with variable amounts of granular material and other organelles, whereas the BS consisted of an electron‐dense core and an outer area with radially oriented filaments. The cerebral cortex was immuno‐reactive with antibodies against tyrosine hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Their PAS positivity, but negativity for ubiquitin and ␣-synuclein (as shown in Table 3 and Figure 1) clearly differentiates them from Lewy bodies. 14,15,19 Collins bodies are also easily distinguished from the more basophilic, argyrophilic, and tau-positive bodies of classic Pick's disease 6,20 (Table 3). They do not appear to be related to protein dense microspheres or spherons, which have recently been shown to contain the A␤ precursor protein and the A␤ 1-40 peptide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their PAS positivity, but negativity for ubiquitin and ␣-synuclein (as shown in Table 3 and Figure 1) clearly differentiates them from Lewy bodies. 14,15,19 Collins bodies are also easily distinguished from the more basophilic, argyrophilic, and tau-positive bodies of classic Pick's disease 6,20 (Table 3). They do not appear to be related to protein dense microspheres or spherons, which have recently been shown to contain the A␤ precursor protein and the A␤ 1-40 peptide.…”
Section: Discussionmentioning
confidence: 99%
“…The results are presented in Figure 1 and in Table 3. As shown (Table 3; Figure 1F) the inclusions are negative for both ubiquitin and ␣-synuclein, and thus they are distinguishable from Lewy bodies [13][14][15] ; they contain neither A␤ nor other abnormal proteins or peptides char- acteristic of Alzheimer's disease. Furthermore, none of the following proteins are detected: intermediate filaments or other cytoskeletal proteins, PGP9.5, ␣ B-crystallin, heat shock proteins 27 or 70, superoxide dismutase, or tau (Table 3).…”
Section: Light Microscopymentioning
confidence: 99%
“…The second type of LB was composed almost entirely of circular or oval fibrillar material and appeared to be the LB of uniform density with light microscopy. Other groups have also reported that LB have a matted network of filaments in the core surrounded by a looser array of radiating filaments in the halo (28)(29)(30).…”
Section: Description and Composition Of Lb Light Microscopymentioning
confidence: 99%
“…In addition, in FAD linked to the APP 717 mutation, extrapyramidal features were present in all members of a single family and LB were present in a proportion of individuals [147]. Moreover, cortical LB in DLB are composed of intermediate filaments (IF) and a granular matrix, while brain stem LB have an electron-dense core and radially oriented filaments [65]. These results suggest that it is degeneration of a specific anatomical pathway, e.g., the extrapyramidal system, that could determine the molecular pathology, e.g., in this case, a-synuclein-immunoreactive LB.…”
Section: Independence Of Primary Determinantsmentioning
confidence: 99%
“…Cellular inclusions in these disorders, however, are also associated with additional molecular constituents. Hence, PB in PiD are immunoreactive to ubiquitin and Alz-50 [111] and in the synucleinopathy DLB [27], LB are also reactive for intermediate filaments (IF) [65], neurofilament (NF) proteins [66], cyclin dependent kinase-5 [34], a-B crystallin [112], and polyubiquitinated chains [86]. Furthermore, aggregates of abnormal intermediate filaments (IF) immunoreactive for a-internexin have been identified as a component of inclusions in neuronal intermediate filament inclusion disease (NIFID), a rare subtype of FTLD [10,30,36,92].…”
Section: Moleculesmentioning
confidence: 99%